Herbal Highs: Review on Psychoactive Effects and Neuropharmacology - Graziano, Silvia (Curr Neuropharmacol, 2017)
BACKGROUND: A new trend among users of new psychoactive substances’ the consumption of “herbal highs”: plant parts containing psychoactive substances. Most of the substances extracted from herbs, in old centuries were at the centre of religious ceremonies of ancient civilizations. Currently, these herbal products are mainly sold by internet web sites and easily obtained since some of them have no legal restriction. OBJECTIVE: We reviewed psychoactive effects and neuropharmacology of the most used “herbal highs” with characterized active principles, with studies reporting mechanisms of action, pharmacological and subjective effects, eventual secondary effects including intoxications and/or fatalities METHOD: The PubMed database was searched using the following key.words: herbal highs, Argyreia nervosa, Ipomoea violacea and Rivea corymbosa; Catha edulis; Datura stramonium; Piper methysticum; Mitragyna speciosa. RESULTS: Psychoactive plants here reviewed have been known and used from ancient times, even if for some of them limited information still exist regarding subjective and neuropharmacological effects and consequent eventual toxicity when plants are used alone or in combination with “classical” drugs of abuse. CONCLUSION: Some “herbal highs” should be classified as harmful drugs since chronic administration has been linked with addiction and cognitive impairment; for some others taking into consideration only the recent trends of abuse, studies investigating these aspects are lacking.